MqsR/MqsA Toxin/Antitoxin System Regulates Persistence and Biofilm Formation in Pseudomonas putida KT2440 - Sun, Chenglong; Guo, Yunxue; Tang, Kaihao; Wen, Zhongling; Li, Baiyuan; Zeng, Zhenshun; Wang, Xiaoxue (Frontiers in Microbiology, 2017)
Bacterial toxin/antitoxin (TA) systems have received increasing attention due to their prevalence, diverse structures, and important physiological functions. In this study, we identified and characterized a type II TA system in a soil bacterium Pseudomonas putida KT2440. This TA system belongs to the MqsR/MqsA family. We found that PP_4205 (MqsR) greatly inhibits cell growth in P. putida KT2440 and Escherichia coli, the antitoxin PP_4204 (MqsA) neutralizes the toxicity of the toxin MqsR, and the two genes encoding them are co-transcribed. MqsR and MqsA interact with each other directly in vivo and MqsA is a negative regulator of the TA operon through binding to the promoter. Consistent with the MqsR/MqsA pair in E. coli, the binding of the toxin MqsR to MqsA inhibits the DNA binding ability of MqsA in P. putida KT2440. Disruption of the mqsA gene which induces mqsR expression increases persister cell formation 53-fold, while overexpressing mqsA which represses mqsR expression reduces persister cell formation 220-fold, suggesting an important role of MqsR in persistence in P. putida KT2440. Furthermore, both MqsR and MqsA promote biofilm formation. As a DNA binding protein, MqsA can also negatively regulate an ECF sigma factor AlgU and a universal stress protein PP_3288. Thus, we revealed an important regulatory role of MqsR/MqsA in persistence and biofilm formation in P. putida KT2440.